EDUKASI PENCEGAHAN PENYEBARAN COVID-19 DENGAN MENERAPKAN PROTOKOL KESEHATAN DI KELURAHAN MATRAS - Ferni Anjani Putri; Vita Selly (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2021)
During this COVID-19 period, people, especially in Matras Village, are required to always adopt a healthy lifestyle and be able to maintain a healthy body by always implementing health protocols as a form of prevention to avoid COVID-19 and break the chain of spreading the corona virus. As for the purpose of this service activity as a form of education to prevent the spread of COVID-19 by implementing health protocols, as an effort to break the chain of transmission of COVID-19. The method used in this service activity is Participatory by involving a group of people in Matras Village such as Youth Organization, Kelompok Sadar Wisata (POK DARWIS), Kepala Lingkungan (KALING), local households and Matras Village Officials. The following are several stages of health program activities carried out including Virtual Socialization Regarding the COVID-19 Health Protocol, Distribution of Masks and Hand Sanitizers and Distribution of banners and posters. All health programs carried out are expected to provide understanding and awareness to the community to always comply with health protocols in all activities carried out in an effort to prevent transmission of COVID-19 and break the chain of spreading the corona virus.